Empowering Children of TPQ Nurul Iman Warak in Learning to Read Quran - Nadhia Rahmawati; Dwijayanti, Ita (Jurnal Pengabdian Masyarakat Inovatif, 2024)
This research project examines the role of students in community service activities, with a particular focus on the Taman Pendidikan Quran (TPQ) Nurul Iman in Warak, Salatiga, Central Java. A TPQ, or Taman Pendidikan Al-Quran, is a non-formal educational institution in Indonesia that specializes in teaching children the Quran, the holy book of Islam. These institutions typically offer lessons in reading, understanding, and memorizing the Quran. Additionally, TPQs often provide Islamic education, teaching young learners about the basic principles of Islam, such as prayers, fasting, and the Five Pillars of Islam. The objective of this activity is to enhance the efficacy of the TPQ in terms of the quality of learning to read the Quran and knowledge of Islamic history. The methodology employed is that of Qur'anic and historical studies. The results of the activity demonstrate that TPQ plays a pivotal role in enhancing the proficiency in Quranic reading through the implementation of multifaceted and experiential pedagogical approaches. Furthermore, TPQ has effectively instilled a comprehensive understanding of Islamic history through the incorporation of historical materials into the instructional curriculum. This activity proposes the formulation of a more structured curriculum and the provision of training for educators to further optimize TPQ's capacity in fostering a profound religious comprehension among learners.